The orbitomeningeal band as a way to bloodless transcavernous dissection and anterior clinoidectomy - Cherian, Iype; Kasper, Ekkehard; Agarwal, Amit (Asian Journal of Neurosurgery, 2018)
The meningo-orbital band (MOB) is a dural fold which runs along the lateral border of the superior orbital fissure and contains few small dural veins and the orbitomeningeal artery. MOB detachment is relatively easy to understand step-wise procedure, provides a wider exposure, and better orientation thus facilitating relatively easy approach to paraclinoid and cavernous sinus region. The present microsurgical technique helps to preserve the true cavernous membrane and thereby providing almost bloodless dissection of the cavernous sinus. The same technique can be used to uncover the anterior clinoid process laterally, posteriorly, superiorly, and also in the inferolateral region thereby decreasing the risk and time of clinoidectomy.
Keywords: Anterior clinoid process; clinoidectomy; orbitomeningeal band; paraclinoid region